ADAPTASI SKALA ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Yosef Arya Wicaksana; Mirna Efar; Meirlyn D. Mewengkang; Indira Miranti; Magdalena Halim; Christiany Suwartono (MANASA, 2012)
Organizational Citizenship Behavior (OCB) which was originated by Organ in 1988 has continuously developed theoritically and practically in organizational study. In 1990, Podsakoff and colleagues had developed a scale usually used in OCB research, named OCB Self-Rating Scale. Researchers adapted the scale into organizational context in indonesia. The research pasticipants are 287 people who work in organzations. After being translated into Indonesian, the psychometric test result showed that some numbers of items are not valid tp measure the domain behavior and OCB construct. This OCB adaptation scale is not valid, either internally or externally, with coefficients of 0,37 and 0,22 respectively. Based on Coefficient Alpha technic of reliability, this scale is reliable with coefficient of 0,81. The norms are categorized by gender. The use of this adaptation scale has to some of the items associated with the organizational contect in Indonesia.